Infuence of zinc and gallic acid on haematological alterations, hepatic and intestinal toxicity induced by sub‑acute exposure to Dibutyl‑n‑phthalate (DBP) in Wistar rats (2022)
Objective Dibutyl-n-phthalate (DBP) is utilized industrially as a plasticizer, as well as in consumer products, food processing and medical applications, but there are concerns over its safety. This study investigated the protective effect of Zinc sulphate (Zn) and Gallic acid (GA) against haematological, hepatic and intestinal alterations following sub-acute (14-day) DBP exposure in rats. Methods Twenty-four male Wistar rats weighing 150–190g were randomly allocated into 4 groups (n=6). Group A (Control) received normal saline at 2 ml/kg. Group B was given DBP (500 mg/kg bw/day) by oral gavage for 14 days. Groups C and D were treated concurrently with Zn (250 mg/kg bw) and GA (120 mg/kg bw), respectively, in addition to DBP treatment. Results Administration of DBP resulted in significant (p<0.05) elevation of serum Alanine transmainase and alkaline phosphatatse, signifcant (p<0.05) increase in faecal counts of coliforms and Escherichia coli (Proteobacteria), as well as reduced colonic mucus production and goblet cell numbers. Histological evidence of DBP toxicity included severe congestion of hepatic central venules, severe infammatory cell infltration in liver and colonic tissues, and atrophy of colonic mucosal glands, with a reduction in erythrocyte count being the major haematological alteration. The protective efects of Zn and GA were manifested as signifcant reduction in the activities of serum enzymes and the severity of hepatic and colonic lesions, along with preservation of haematological indices and colonic mucus. GA caused signifcant reduction in E. coli and coli forms, while also increasing enterococci count. Conclusion Dietary supplementation with Zn or GA may alleviate DBP-induced liver and colonic toxicity. The probable mechanisms may include the preservation of the colonic mucus barrier and improvement in the abundance of beneficial bacteria.